Population history and the selective landscape shape patterns of osmoregulatory trait divergence in tidal marsh Savannah sparrows (Passerculus sandwichensis). (28th November 2019) - Benham, Phred M.; Cheviron, Zachary A.
Abstract: A persistent challenge in making associations between phenotypic and environmental variation is understanding how ecological factors and demographic history interact to shape adaptive outcomes. Evaluating the degree to which conspecific populations exposed to similar environmental pressures respond in parallel provides a powerful framework for addressing this challenge. We took this comparative approach with multiple populations of Savannah sparrows ( Passerculus sandwichensis ) found in tidal marshes along the Pacific coast of North America. The high salinities characterizing tidal marshes select for increased osmoregulatory performance and salinity tolerance. We collected data on physiological traits associated with osmoregulatory performance from 10 tidal marsh and three freshwater‐adapted interior populations to evaluate the degree of parallel divergence across populations. All traits showed differences in the magnitude of divergence, but only total evaporative water loss (TEWL) showed differences in the direction of divergence. The drivers of these differences in both the magnitude and direction of divergence varied among traits. For kidney morphology and TEWL, patterns of divergence were best explained by variation in immigration rate from interior populations. Maximum temperature was the best predictor of variation in urine excretion ability, and both gene flow and temperature contributed to variation in plasma osmolality. Finally, analysis of multitrait divergence patterns indicated that differences in the direction of divergence were best explained by population genetic structure, whereas differences in the magnitude of divergence were explained by environmental differences. Together these results show that the influences of demography and the selective landscape can manifest themselves differently across functionally integrated traits.